2010
DOI: 10.1108/14691931011013307
|View full text |Cite
|
Sign up to set email alerts
|

Visualising and measuring intellectual capital in capital markets: a research method

Abstract: Purpose -The purpose of this paper is to describe a research method successfully used to study intellectual capital (IC) and IC flows through a highly networked marketplace. Design/methodology/approach -The method integrates computer-assisted content analysis (CA) and multivariate statistics. The CA is performed on a large source of business and analyst reports. The method is successful in enabling the elements of IC to be related to firm performance, using 156 firms in the global information technology market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 50 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…Not using technology means that results are unreliable and that most research is limited to small sample sizes. However, as Goebel (2015) demonstrates, it is possible to use technology with larger sample sizes because it adds to coding reliability and continuity and enhances the reliability of results (Lock Lee and Guthrie, 2010; Dumay and Cai, 2014). The main problem with not using appropriate technology to enhance reliability is that the research inherits the prior mistakes of other research and compounds errors.…”
Section: The Problem With Icd Researchmentioning
confidence: 99%
“…Not using technology means that results are unreliable and that most research is limited to small sample sizes. However, as Goebel (2015) demonstrates, it is possible to use technology with larger sample sizes because it adds to coding reliability and continuity and enhances the reliability of results (Lock Lee and Guthrie, 2010; Dumay and Cai, 2014). The main problem with not using appropriate technology to enhance reliability is that the research inherits the prior mistakes of other research and compounds errors.…”
Section: The Problem With Icd Researchmentioning
confidence: 99%
“…The advantage of using an unmodified ICD index is that it can facilitate comparison between different research projects. However, the accuracy and comparability of CA results decrease as the number of terms used increases because they are utilised differently and can thus have conflicting meanings (see Lock Lee and Guthrie, 2010). Additionally, there are 45 articles using ICD indexes based on different sources or that do not disclose the source, which infers that many CA ICD researchers do not pay much attention to the potential need to replicate studies in different contexts.…”
Section: Icd Indexmentioning
confidence: 99%
“…Bollen, Vergauwen  Schneiders (2005) examine the relationship between IC components, intellectual property and performance of pharmaceutical companies in Germany, where they confirmed that IC components (HC, SC and RC) are mutually correlated. Lee  Guthrie (2010) analyse IC through HC, internal and external capital and conclude that there is a strong and positive correlation between HC and internal capital and internal and external capital, while the correlation between HC and external capital could be defined as a medium one.…”
Section: Intellectual Capital Componentsmentioning
confidence: 99%